Enhanced Water-Splitting Performance of Perovskite SrTaO2N Photoanode Film through Ameliorating Interparticle Charge Transport - Zhong, Yujiao; Li, Zhaosheng; Zhao, Xin; Fang, Tao; Huang, Huiting; Qian, Qinfeng; Chang, Xiaofeng; Wang, Peng; Yan, Shicheng; Yu, Zhentao; Zou, Zhigang (Advanced functional materials, 2016)
Here SrTaO2N has been found to exhibit photoelectrochemical water splitting, with a theoretical solar‐to‐hydrogen efficiency of 14.4%. Ameliorating the interparticle charge transport by H2 annealing, the solar photocurrent of the SrTaO2N(H) granular film at 1.23 V versus reversible hydrogen electrode (RHE) is increased by ≈250% in comparison with the SrTaO2N film. Using an aberration corrected scanning transmission electron microscope and super‐X energy dispersive spectroscopy, the atomic scale observation has proved a decrease of oxygen concentrations in the surface of SrTaO2N(H) particle, which may allow its electrical conductivity to be increased from 0.77 × 10−6 to 2.65 × 10−6 S cm−1 and therefore the charge separation efficiency has been greatly increased by ≈330%. After being modified by Co–Pi water oxidation catalyst, the SrTaO2N(H) photoanode shows a solar photocurrent of 1.1 mA cm−2 and an incident photo‐to‐current efficiency value of ≈20% at 400–460 nm and 1.23 V versus RHE, which suggests that it is a new promising photoanode material for solar water splitting. SrTaO2N is found to be a new promising photoanode for photoelectrochemical water splitting. The atomic scale observation proves a decrease of oxygen concentrations in the surface of SrTaO2N(H) particle after H2 annealing, which may improve its bulk electrical conductivity and the charge separation efficiency. Consequently, the photoelectrochemical performance of SrTaO2N(H) granular film is enhanced remarkably.